A Computational Analysis of Different Geometric Ratios at the Input of a Secondary Fluid that Affects the Efficiency of a Subsonic Air-Air Ejector - HINCAPIE-MONTOYA, Jhon Fredy; SIERRA-DEL-RIO, Jorge Andres; TORRES-LOPEZ, Edwar Andres; HINCAPIE-ZULUAGA, Diego Andres (Engineering Transactions, 2021)
For this study, the computational fluid dynamics (CFD) technique was used to investigate the combined effects of different geometric parameter relationships; inclination angle variation of the secondary fluid inlet, different lengths of the mixing chamber, and different separation values between the nozzle outlet and the input of the mixing chamber, in an air-air ejector used in a subsonic regime. As a working fluid, the air was used as an ideal gas and its viscosity was expressed as a constant both in the primary and secondary fluids. The renormalization group (RNG) κ-ε turbulence model was used to predict more accurately the way the pressure recovers along the ejector and suitability/applicability to for recirculation flows. It was found in the numerical results that there is an optimal value of the inclination angle for the secondary fluid inlet, the length of the mixing chamber and the separation between the nozzle outlet and the mixing chamber inlet, where the ejector obtains its maximum mass flow ratio. In addition, it was found that the efficiency of the air-air ejector is related to the inclination angle of the secondary fluid inlet.